2007
DOI: 10.1016/j.ejpain.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pain‐related fear on sexual arousal in women with superficial dyspareunia

Abstract: The role of pain-related fear in the etiology and/or maintenance of superficial dyspareunia is still unclear. The objective of this experiment was to investigate the effects of pain-related fear on sexual arousal in women with superficial dyspareunia (n=48) and women without sexual complaints (n=48). To induce pain-related fear, participants were told that they had a 60% chance of receiving painful stimuli while being exposed to one of two erotic film clips. Genital arousal was assessed using vaginal photoplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
77
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 47 publications
17
77
1
Order By: Relevance
“…Research conducted in laboratory settings indicates that there are no significant differences between women with vulvovaginal pain and non afflicted women relative to their physiological level of sexual arousal when exposed to an erotic stimulus, although women with pain tend to report more negative feelings toward the stimulus [13][14][15].…”
Section: Explanation To the Answers To Questionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research conducted in laboratory settings indicates that there are no significant differences between women with vulvovaginal pain and non afflicted women relative to their physiological level of sexual arousal when exposed to an erotic stimulus, although women with pain tend to report more negative feelings toward the stimulus [13][14][15].…”
Section: Explanation To the Answers To Questionmentioning
confidence: 99%
“…Specifically, controlled studies have shown that they report significantly less sexual desire, arousal and satisfaction, more difficulty reaching orgasm, as well as lower frequencies of intercourse and more negative attitudes toward sexuality than pain-free controls [12]. Research conducted in laboratory settings indicates that there are no significant differences between women with vulvovaginal pain and non afflicted women relative to their physiological level of sexual arousal when exposed to an erotic stimulus, although women with pain tend to report more negative feelings toward the stimulus [13][14][15].…”
Section: A Psychological Sexual and Relationship Consequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, critical for the development of dyspareunia is the lack of genital arousal that is marked by insufficient lubrication and driven by anticipation-anxiety. In support of this model, research has shown that women react with involuntary pelvic floor muscle activity in response to threatening sexual stimuli [34] and impeded genital arousal -as measured through vaginal pulse amplitude signals -in response to appraisal (i.e., suggestion that a female actor experiences pain) and pain threat (i.e., threat of electrical pulses on the ankle) manipulations [6,7].Genital responsiveness was, however, not different in women with dyspareunia compared to healthy controls, although they did report lower subjective sexual arousal. Note that such discordance between physiological (i.e., genital) and psychological (i.e., subjective experience of) sexual arousal is commonly observed in women [26].…”
mentioning
confidence: 99%